Часы с лягушкой: [повесть] / Валерий Гусев - Гусев Валерий Борисович (Черный котенок, 2015)
Экземпляры: ф.12 (20150921) / Инвентарный номер: 47111 / Цена: 151.00 / Авт.знак: Г 96 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6